Model and Method for Request Signals Processing of Secondary Surveillance Radar - Свид, І. В.; Обод, І. І.; Мальцев, О. С.; Заволодько, Г. Е.; Штих, І. А.; Майстренко, Г. В. (CADSM, 2019)
In the present work, based on a comparative analysis of the quality of signal processing of the request Secondary Surveillance Radar (SSR), it is shown that the model and method of processing signals of the SSR request are based on a two-channel construction principle and in which the normalized signals from the output of the threshold device are used for signal selection by time of the main channel of concurrency, allows to improve the quality of processing such request signals in comparison with single-channel processing by the concurrency method by reducing the influence of false signals in the side lobes of signal request uncertainty function.
Keywords: Secondary Surveillance Radar; SSR; request signal; uncertainty function; time interval code